2019
DOI: 10.3390/molecules24183240
|View full text |Cite
|
Sign up to set email alerts
|

Chaetomadrasins A and B, Two New Cytotoxic Cytochalasans from Desert Soil-Derived Fungus Chaetomium madrasense 375

Abstract: Two new cytochalasans, Chaetomadrasins A (1) and B (2), along with six known analogues (3–8), were isolated from the solid-state fermented culture of desert soil-derived Chaetomium madrasense 375. Their structures were clarified by comprehensive spectroscopic analyses, and the absolute configurations of Compounds 1 and 2 were confirmed by electronic circular dichroism (ECD) and calculated ECD. For the first time, Chaetomadrasins A (1), which belongs to the chaetoglobosin family, is characterized by the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Our work, together with those focused on the screening for bioactive metabolites produced by members of the Sordariales [ 5 , 6 , 9 ], confirms the potential of this fungal order as a producer of bioactive compounds. In particular, the new genus Pseudorhypophila includes species able to produce a plethora of bioactive compounds, including the widely studied antifungal sordarins.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our work, together with those focused on the screening for bioactive metabolites produced by members of the Sordariales [ 5 , 6 , 9 ], confirms the potential of this fungal order as a producer of bioactive compounds. In particular, the new genus Pseudorhypophila includes species able to produce a plethora of bioactive compounds, including the widely studied antifungal sordarins.…”
Section: Discussionsupporting
confidence: 70%
“…Numerous members of the Sordariales are being tested for the production of novel biologically active compounds during the course of an ongoing project, since this group of fungi has been demonstrated to contain prolific producers [ 5 , 6 ]. A prominent example is the production of the antimycotic sordarins by several taxa belonging to this order, e.g., Rhypophila pleiospora [ 7 ] and Zopfiella marina [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The conformers of 3 were identified via ECD simulation using the time-dependent density functional theory (TD-DFT) method at the B3LYP/6-31+G (d, p) level with methanol as solvent, and the rotational strengths of 30 excited states were calculated. ECD spectra of compound 3 were obtained using the SpecDis 1.6 (University of Würzburg, Würzburg, Germany) and GraphPad Prism 5 (University of California San Diego, USA) software by applying Gaussian band shapes with sigma = 0.3 eV from dipole-length rotational strengths (Guo et al, 2019).…”
Section: Quantum-chemical Calculationmentioning
confidence: 99%
“…This transformation could increase the nitrogen content and nucleophilic character of further reactions (Feher and Schmidt, 2003). In previous studies, we reported several bioactive cytochalasans that were isolated from C. madrasense 375 derived from desert soil (Guo et al, 2019). To gain more novel cytochalasan-like bioactive compounds, a chemical transformation of crude broth extracts of C. madrasense 375 with hydrazine monohydrate was performed, followed by purification of reaction products, which offered three new cytochalasans derivatives chaetoglobosins B 1 -B 3 (1-3), and known chaetoglobosin B (4) (Sekita et al, 1982(Sekita et al, , 1983 chaetoglobosin D (5) (Sekita et al, 1982(Sekita et al, , 1983, chaetoglobosin E (6) (Sekita et al, 1976), and cytoglobosin A (7) (Cui et al, 2010) were also isolated from the unreactive raw extract of this fungus.…”
Section: Introductionmentioning
confidence: 99%
“…Chaetoglobosin A and chaetoglobosin variants have been described from Chaetomium globosum ( Turner and Aldridge, 1983 ; Jiao et al, 2004 ; Xue et al, 2012 ; Chen et al, 2016 ; Jiang et al, 2016 ), other Chaetomium species ( Sekita et al, 1982 ; Turner and Aldridge, 1983 ; Kawahara et al, 2013 ; Guo et al, 2019 ), Cylindrocladium floridanum ( Ichihara et al, 1996 ), Ijuhya vitellina ( Ashrafi et al, 2017 ), Penicillium chrysogenum ( Zhu et al, 2017 ), Penicillium expansum ( Andersen et al, 2004 ), Phomopsis leptostromiformis ( Burlot et al, 2003 ), and Stenocarpella macrospora and Stenocarpella maydis ( Cutler et al, 1980 ; Springer et al, 1980 ; Rogers et al, 2014 ). However, to the best of our knowledge, chaetoglobosin P has not been reported elsewhere since the original report ( Donoso et al, 1997 ).…”
Section: Introductionmentioning
confidence: 99%